Precision patients: Selection practices and moral pathfinding in experimental oncology. Issue 2 (7th January 2022) - Dam, Mie S.; Green, Sara; Bogicevic, Ivana; Hillersdal, Line; Spanggaard, Iben; Rohrberg, Kristoffer S.; Svendsen, Mette N.
Abstract: This paper addresses selection practices in a Danish phase 1 unit specialised in precision medicine in the field of oncology. Where precision medicine holds the ambition of selecting genetically fit medicine for the patient, we find that precision medicine in the early trial setting is oriented towards selecting clinically and genetically fit patients for available treatment protocols. Investigating how phase 1 oncologists experience and respond to the moral challenges of selecting patients for early clinical trials, we show that inclusion criteria and patient categories are not always transparent to patients. Lack of transparency about inclusion criteria has been interpreted as morally problematic. Yet drawing on social science studies of 'unknowing', we argue that silence and non‐transparency in interactions between oncologists and patients are crucial to respect the moral agency of patients at the edge of life and recognise them as belonging to the public of Danish health care. In the discussion, we consider the practice of placing 'unfit' patients on a waiting list for trial participation. Rather than representing an ethical and political problem, we argue, the waiting list can act as a valve enabling oncologists to navigate the scientific and as well as the moral uncertainties in phase 1 oncology.